Hydrogen formation from a real biogas using electrochemical cell with gadolinium-doped ceria porous electrolyte. Issue 4 (March 2017) - Hirata, Yoshihiro; Shimonosono, Taro; Ueda, Koki; Sameshima, Soichiro; Yamaji, Katsuhiko
Abstract: The electrochemical cell consisting of a gadolinium-doped ceria (GDC, Ce0.9 Gd0.1 O1.95 ) porous electrolyte, Ni–GDC cathode and Ru–GDC anode was applied for the dry-reforming (CH4 +CO2 →2H2 +2CO) of a real biogas (CH4 60.0%, CO2 37.5%, N2 2.5%) produced from waste sweet potato. The composition of the supplied gas was adjusted to CH4 /CO2 =1/1 volume ratio. The supplied gas changed continuously into a H2 –CO mixed fuel with H2 /CO=1/0.949–1/1.312 vol ratios at 800 °C for 24 h under the applied voltage of 1–2 V. The yield of the mixed fuel was higher than 80%. This dry-reforming reaction was thermodynamically controlled at 800 °C. The application of external voltage assisted the reduction of NiO and the elimination of solid carbon deposited slightly in the cathode. The decrease of heating temperature to 700 °C reduced gradually the fraction of the H2 –CO fuel (61.3–18.6%) within 24 h. Because the Gibbs free energy change was calculated to be negative values at 700–600 °C, the above result at 700–600 °C originated from the gradual deposition of carbon over Ni catalyst through the competitive parallel reactions (CH4 →C+2H2, 2CO→C+CO2 ). The application of external voltage decreased the formation temperature of carbon by the disproportionation of CO gas. At 600 °C, the H2 –CO fuel based on the Faraday's law was produced continuously by the electrochemical reforming of the biogas.